Buildings with less HVAC power demand by incorporating PCM into envelopes taking into account ASHRAE climate classification. (1st July 2022) - Kalbasi, Rasool; Hassani, Parsa
Abstract: In this study, focusing on comfort time, the effect of phase change material (PCM) presence in ten climatic zones with an average temperature of 13.1–26.9 °C, cooling degree-days of 2500–6700 and heating degree-days of 400–2800 were discussed. Numerical results were deduced by developing energy equations for the whole building along with momentum and continuity equations for PCM. The results showed that for all regions adding PCM significantly increases comfort time. If the PCM is installed closer to the indoor, its comfort time is longer than other locations. To select a suitable PCM, five materials with a melting temperature in the range of 18–24 °C were selected and it was observed that a suitable PCM has a slight dependence on the comfort temperature range. By defining the comfort range 18–27 °C, it was found that for a simple building (without PCM), the comfort time percent varied in the range of 26–40%. With the addition of PCM, it was observed that the comfort time percent varied in the range of 54–82%. In other words, in the presence of a suitable PCM without energy consumption, the internal temperature can be set in the range of 18–27 °C up to 82% in a year. In this scenario, PCM-22 was suitable for six regions (out of ten regions). For scenarios of 20–25 °C, it was found that PCM-23 was suitable for eight regions. If PCM-23 was added to conventional buildings, without energy consumption at least in 54% of a year, the temperature can be set in the range of 20–25 °C . Highlights: Focusing on comfort time, the effect of PCM presence in ten climatic zones was examined. For all regions, adding PCM significantly increases comfort time. Comfort time percent was in the range of 26–40% for simple building Comfort time percent was in the range of 54–82% for PCM enhanced building For comfort range 20–25 °C, at least in 54% of a year, there is no need for energy consumption